(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
In this article the choice of parameters of the current collection systems is substantiates, which must be monitored by technical means. It is shown that such parameters are the intensity of the sparking under brushes, uniformity of current distribution on parallel brushes, vibrations and runout slip rings and the state of their surface. For monitoring these parameters Ecotech Ltd (Pskov) develops a hardware-software complex. Complex consists of the following devices: - device to monitor the intensity of sparking, - device for measuring the current of brushes, - device for measuring vibrations and runout, - device for exploring the surface of rotating slip rings. Development of hardware-software complex is supported by the Foundation for Assistance to Small Innovative Enterprises in the scientific and technical field.